Janet Flanner’s The Cubical City and the Life She Left Behind - Rai PETERSON (E-REA)
Reading Janet Flanner’s novel, The Cubical City (1926), as a lesbian modernist novel provides insight, not only into the author’s personal turmoil around coming out, but into broader work on the lesbian identity that was evolving during the modernist period in transatlantic literature. Flanner’s novel includes minor lesbian characters and sub-plots, yet on the surface it seems to be a heteronormative romance in which a promiscuous female character pursues marriage with an eligible bachelor. Furthermore, the novel subtly explores coming out issues between mothers and daughters, a fraught topic that has not been written about frequently, especially during the early twentieth century. While Flanner’s protagonist is trapped into marriage, Flanner herself escaped a similar fate by fleeing to Paris as an expatriate. Recent critical attention has shed light on lesbian roman à clef works by English and American expatriates published in 1928, including Djuna Barnes’ Ladies Almanack, Radclyffe Hall’s The Well of Loneliness, and Virginia Woolf’s Orlando. This reading of The Cubicle City locates it as foundational to lesbian modernist novels and as an artifact which demonstrates the freedom that transnationality conferred upon Flanner, yet was denied her protagonist.